2017
DOI: 10.1080/00071005.2017.1343454
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Bricoleurs and Bricolage Researchers: The case of Religious Education

Abstract: This article reconceptualises school teachers and pupils respectively as 'pedagogical bricoleurs' and 'bricolage researchers' who utilise a multiplicity of theories, concepts, methodologies and pedagogies in teaching and/or researching. This reconceptualization is based on a coalescence of generic curricular and pedagogical principles promoting dialogic, critical and enquiry-based learning. Innovative proposals for reconceptualising the aims, contents and methods of multi-faith Religious Education in English s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
0
20
0
9
Order By: Relevance
“…A recent study from Uganda [40] found that regardless of the resourceconstrained context and pedagogical challenges experienced by academics, their attitude demonstrated resilience, flexibility and determination to embrace ICT in their teaching practice. This study challenges the notion of academics being passive, 'making do' with what is at hand [41] and claims that academics are resourceful practitioners, seeking inventive ways to teach more effectively.…”
Section: Discussionmentioning
confidence: 70%
“…A recent study from Uganda [40] found that regardless of the resourceconstrained context and pedagogical challenges experienced by academics, their attitude demonstrated resilience, flexibility and determination to embrace ICT in their teaching practice. This study challenges the notion of academics being passive, 'making do' with what is at hand [41] and claims that academics are resourceful practitioners, seeking inventive ways to teach more effectively.…”
Section: Discussionmentioning
confidence: 70%
“…However, methodologically and pedagogically the subject has in this context become plural, the multiple and sometimes conflicting aims for the subject resulting in a number of different approaches to teaching of it (see Grimmitt, 2000). Recent pedagogies and approaches have sought to rationalize and legitimize this plurality in terms of preparing children and young people to study Theology and Religious Studies at university level, inculcating them into the approaches and methodologies utilized in higher education (Freathy et al, 2017).…”
Section: Religious Education As Preparation For the Academic Study Ofmentioning
confidence: 99%
“…RE needs to deal with ongoing global trends such as the reality of religious plurality (Berger 2014;Riegel and Delling 2014), individualization of religions (Jackson 2014;Woodhead and Catto 2012), and the consequences of secularization (Taylor 2007). The wide ongoing debate about developing RE in many Western countries has focused on what kind of knowledge RE should provide and what skills and competencies are most relevant today (Freathy et al 2017;Skeie 2014;Conroy 2016;CoRe 2018;Clarke and Woodhead 2017). In addition, RE has been faced with new conceptions of learning pedagogy, namely "new learning".…”
Section: Introductionmentioning
confidence: 99%